2010
DOI: 10.1614/ipsm-d-10-00019.1
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fingerprinting to Improve Data Collection Efficiency and Yield in an Open-Field Host-Specificity Test of a Weed Biological Control Candidate

Abstract: An open-field test was conducted in southern France to assess the host-specificity of Ceratapion basicorne (Illiger), a candidate for biological control of yellow starthistle. Test plants were infested by naturally occurring populations of C. basicorne but were also exposed to sympatric herbivore species, including other Ceratapion spp. Insects from the test plants were collected directly into tubes of ethanol and were subsequently identified to species according to DNA sequence similarity with morphologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The PCR cycle was performed using the Folmer’s primers LC01490 and HC02198 [ 42 ]; complete details of the laboratory procedures are reported in Rector et al . [ 43 ]. The acquired sequences, deposited at the European Nucleotide Archive with accession numbers LN612634-LN612636, were screened for identification by a blast search over the National Center for Biotechnology Information (NCBI) GenBank nucleotide collection using the Mega BLAST procedure [ 44 ] available at its website ( http://www.ncbi.nlm.nih.gov/blast ).…”
Section: Methodsmentioning
confidence: 99%
“…The PCR cycle was performed using the Folmer’s primers LC01490 and HC02198 [ 42 ]; complete details of the laboratory procedures are reported in Rector et al . [ 43 ]. The acquired sequences, deposited at the European Nucleotide Archive with accession numbers LN612634-LN612636, were screened for identification by a blast search over the National Center for Biotechnology Information (NCBI) GenBank nucleotide collection using the Mega BLAST procedure [ 44 ] available at its website ( http://www.ncbi.nlm.nih.gov/blast ).…”
Section: Methodsmentioning
confidence: 99%
“…The reason given for the negative decision by USDA APHIS was that ''… this insect may negatively impact a United States crop plant (safflower)'' and was likely based on data showing that under no-choice conditions, the weevil's fundamental host range included safflower (Carthamus tinctorius L.) (Smith 2007), a crop plant grown for oil production. However, in tests examining the realized host range of the weevil, safflower was not attacked during five open-field experiments (three included in the petition and two conducted subsequently (Cristofaro et al 2013;Rector et al 2010;Smith et al 2006). In addition, C. basicorne has never been reported from safflower in their shared native Eurasian range (Cristofaro et al 2013).…”
mentioning
confidence: 99%
“…They found that 54% of the YST but none of the 1021 safflower plants were attacked by the weevil. In addition, Rector et al () in a field experiment in France found that C. basicorne attacked yellow starthistle and cornflower but not safflower (Antonini et al , ). The rosette weevil is not known to attack safflower in its Palearctic range (Alonso‐Zarazaga, ; Wanat, ) and the host specificity data suggest that it is highly stenophagous (Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…Field observations (Uygur et al , ) and modelling analysis (Gutierrez et al , ) suggest that natural enemies killing whole plants before seed maturation and/or reducing the ability of surviving plants to compensate for feeding damage with reduced seed production are required for successful control (see below). The weevil Ceratapion basicorne (Illiger) (Coleoptera; Brentidae) attacks the rosette stage of YST throughout most of its range in the Mediterranean Basin (Alonso‐Zarazaga, ; Antonini et al , ) and has some of requisite attributes: infestation levels range from 25% to 100% (Uygur et al , ; Smith et al , ) and it is highly host specific (Smith et al , ; Smith, , ; Rector et al , ; Cristofaro et al , ). A release permit application for C. basicorne for North America was submitted to USDA‐APHIS (U.S. Department of Agriculture's Animal and Plant Health Inspection Service) on 26 January 2006 (Smith, ), although approval has not been granted because of concerns about possible risk to safflower crops ( Carthamus tinctorius ) and the ornamental cornflower ( Centaurea cyanus ) that are of Palearctic origin (Hinz et al , ; L. Smith, personal communication).…”
Section: Introductionmentioning
confidence: 99%